Self-Similar Blow-Up Solutions of the KPZ Equation - Alexander Gladkov (International Journal of Differential Equations)
Self-similar blow-up solutions for the generalized deterministic KPZ equation ut=uxx+|ux|q with q>2 are considered. The asymptotic behavior of self-similar solutions is studied.